Secondary battery
By controlling the distribution of solid electrolyte and adhesive in the positive electrode active material layer of all solid lithium secondary batteries, a specific laminated structure is formed, and the problem of insufficient fast charging characteristics of secondary batteries in the prior art is solved, and a higher level is achieved energy density and cyclic characteristics.
Patent Information
- Application Number
- CN202280096137.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-19
- Publication Date
- 2024-12-31
AI Technical Summary
The existing all-solid-state lithium secondary batteries cannot achieve sufficient fast charging characteristics in the positive electrode active material layer.
By controlling the amount of solid electrolyte in the positive electrode active material layer, it is ensured that the solid electrolyte content in the first layer is 1 mass % or more, and the solid electrolyte content in the second layer is 0 mass % or more or more and less than 1 mass % , to improve lithium ion conductivity and adhesive distribution, form a positive electrode active material layer with a laminated structure.
The rapid charging characteristics of the secondary battery are improved, the internal resistance is reduced, and the energy density and cycle characteristics are improved.
Smart Images

Figure CN119234324A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a secondary battery. Background Art
[0002] In recent years, in order to cope with the global warming effect, there is an urgent need to reduce carbon dioxide emissions. In the automotive industry, the introduction of electric vehicles (EVs) and hybrid electric vehicles (HEVs) has led to high expectations for reducing carbon dioxide emissions, and the development of non-aqueous electrolyte secondary batteries such as secondary batteries for motor drives, which are key to their practical application, is being actively carried out.
[0003] Secondary batteries for driving motors are required to have extremely high output characteristics and high energy compared to consumer lithium secondary batteries used in mobile phones, notebook computers, etc. Therefore, lithium secondary batteries, which have the highest theoretical energy of all batteries in reality, have attracted attention and are currently being developed rapidly.
[0004] Here, currently, the lithium secondary battery that is generally used uses a flammable organic electrolyte as an electrolyte. Such liquid lithium secondary batteries have stricter safety measures against leakage, short circuit, overcharge, etc. than other batteries.
[0005] Therefore, in recent years, the research and development of all-solid-state lithium secondary batteries using oxide-based and sulfide-based solid electrolytes for electrolytes is being actively carried out. Solid electrolytes are materials that are composed of ion conductors that can conduct ions in solids as the main body. Therefore, in all-solid-state lithium secondary batteries, various problems caused by flammable organic electrolytes like conventional liquid lithium secondary batteries will not occur in principle. In addition, if high-potential / large-capacity positive electrode materials and large-capacity negative electrode materials are usually used, a substantial increase in the output density and energy density of the battery can be achieved.
[0006] However, in a conventional all-solid-state lithium secondary battery, the positive electrode has a structure in which a positive electrode active material layer is arranged on the surface of a positive electrode current collector. In addition, the positive electrode active material layer further includes a solid electrolyte for improving the lithium ion conductivity in the positive electrode active material layer, and a binder for bonding particles of the positive electrode active material and the solid electrolyte and bonding these particles to the positive electrode current collector.
[0007] Here, in the International Publication No. 2020 / 241691 manual, an all-solid-state battery is disclosed, wherein at least one of the positive electrode layer (positive electrode active material layer), the negative electrode layer (negative electrode active material layer) and the solid electrolyte layer comprises a granular first binder and a non-granular second binder. According to the International Publication No. 2020 / 241691 manual, by setting such a structure, an all-solid-state battery with good cycle characteristics can be provided. Summary of the invention
[0008] Problem that the invention aims to solve
[0009] However, according to the research of the present inventors, it has been proved that when the positive electrode active material layer of the secondary battery adopts the technology described in the pamphlet of International Publication No. 2020 / 241691, there is a case where sufficient fast charging characteristics cannot be obtained in the secondary battery using the positive electrode active material layer.
[0010] Therefore, an object of the present invention is to provide a method for improving rapid charging characteristics in a secondary battery.
[0011] Solutions for solving problems
[0012] The present inventors have conducted intensive research to solve the above problems and have found that the above problems can be solved by controlling the amount of solid electrolyte contained in the surface portion of the positive electrode active material layer on the side in contact with the positive electrode current collector to a specific value or less, thereby completing the present invention.
[0013] That is, one embodiment of the present invention relates to a secondary battery having a power generation element, the power generation element comprising: a positive electrode formed by configuring a positive electrode active material layer on the surface of a positive electrode collector, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode and containing a solid electrolyte. In the secondary battery, the positive electrode active material layer is stacked by a first layer and a second layer, the first layer is in contact with the solid electrolyte layer and contains a positive electrode active material, a solid electrolyte and a binder, and the second layer is in contact with the positive electrode collector and contains a positive electrode active material and a binder. Moreover, relative to 100% by mass of the total solid content contained in the first layer, the content of the solid electrolyte in the first layer is 1% by mass or more, and relative to 100% by mass of the total solid content contained in the second layer, the content of the solid electrolyte in the second layer is 0% by mass or more than 0% by mass and less than 1% by mass. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a perspective view showing the appearance of a flat laminated all-solid lithium secondary battery as one embodiment of the present invention.
[0015] Figure 2 For along Figure 1 A cross-sectional view along line 2-2 is shown.
[0016] Figure 3 This is a cross-sectional view schematically showing a positive electrode according to one embodiment of the present invention.
[0017] Figure 4 This is a schematic diagram showing an example of a branched fibrous binder. DETAILED DESCRIPTION
[0018] One embodiment of the present invention relates to a secondary battery having a power generation element, the power generation element comprising: a positive electrode formed by configuring a positive electrode active material layer on the surface of a positive electrode collector, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode and containing a solid electrolyte. In the secondary battery, the positive electrode active material layer is stacked by a first layer and a second layer, the first layer is in contact with the solid electrolyte layer and contains a positive electrode active material, a solid electrolyte and a binder, and the second layer is in contact with the positive electrode collector and contains a positive electrode active material and a binder. Moreover, relative to 100% by mass of the total solid content contained in the first layer, the content of the solid electrolyte in the first layer is 1% by mass or more, and relative to 100% by mass of the total solid content contained in the second layer, the content of the solid electrolyte in the second layer is 0% by mass or more than 0% by mass and less than 1% by mass. According to this embodiment, the fast charging characteristics can be improved in the secondary battery.
[0019] Hereinafter, the above-mentioned embodiments of the present invention will be described with reference to the accompanying drawings. The technical scope of the present invention shall be determined based on the description of the scope of the claims and shall not be limited to the following methods. It should be noted that the dimensional ratios of the accompanying drawings are sometimes enlarged according to the description and are different from the actual ratios. The present invention is described below by taking a flat stacked (internal parallel) all-solid-state lithium secondary battery as one mode of a secondary battery.
[0020] Figure 1 It is a perspective view showing the appearance of a flat laminated all-solid lithium secondary battery as one embodiment of the present invention. Figure 2 For along Figure 1 The cross-sectional view of line 2-2 is shown. By setting the stacking type, the battery can be miniaturized and have a higher capacity. It should be noted that in this specification, Figure 1 and Figure 2 The flat stacked non-bipolar all-solid-state lithium secondary battery (hereinafter also referred to as "stacked battery") shown in the figure is described in detail. However, from the perspective of the electrical connection method (electrode structure) inside the secondary battery of this method, it can also be applied to any of non-bipolar (internal parallel type) batteries and bipolar (internal series type) batteries.
[0021] like Figure 1 As shown, the stacked battery 10a has a rectangular flat shape, and the negative electrode collector plate 25 and the positive electrode collector plate 27 for extracting electricity are led out from both sides thereof. The power generation element 21 is covered by the battery outer packaging material (laminated film 29) of the stacked battery 10a, and the surrounding is heat-welded, and the power generation element 21 is sealed in a state where the negative electrode collector plate 25 and the positive electrode collector plate 27 are led out to the outside.
[0022] It should be noted that the secondary battery of this method is not limited to a stacked flat secondary battery. In a wound all-solid lithium secondary battery, it can be a cylindrical secondary battery, or it can be deformed into a rectangular flat secondary battery, etc., without special restrictions. In the above-mentioned cylindrical secondary battery, a laminated film can be used as its outer packaging material, or a conventional cylindrical can (metal can) can be used, etc., without special restrictions. Preferably, the power generation element is housed inside the laminated film containing aluminum. In this way, lightweighting can be achieved.
[0023] In addition, for Figure 1 There is no particular limitation on the extraction of the collector plates (25, 27). The negative collector plate 25 and the positive collector plate 27 may be extracted from the same side, or the negative collector plate 25 and the positive collector plate 27 may be divided into a plurality of portions and extracted from each side. Figure 1 The secondary battery shown is not limited. In addition, in a wound-type all-solid lithium secondary battery, the terminal may be formed by changing the tab to, for example, a cylindrical can (metal can).
[0024] like Figure 2 As shown, the stacked battery 10a of this embodiment has the following structure: a flat, roughly rectangular power generation element 21 that actually performs charge and discharge reactions is sealed inside a laminate film 29 that serves as a battery exterior material. Here, the power generation element 21 has a structure formed by stacking a positive electrode, a solid electrolyte layer 17, and a negative electrode. The positive electrode has the following structure: a positive electrode active material layer 15 containing a positive electrode active material is arranged on both sides of a positive electrode collector 11". The negative electrode has the following structure: a negative electrode active material layer 13 containing a negative electrode active material is arranged on both sides of a negative electrode collector 11'. Specifically, the positive electrode, the solid electrolyte layer, and the negative electrode are stacked in sequence in a manner that one positive electrode active material layer 15 and the adjacent negative electrode active material layer 13 are opposite to each other with a solid electrolyte layer 17 sandwiched therebetween. Thus, the adjacent positive electrode, solid electrolyte layer, and negative electrode constitute a single battery layer 19. Therefore, it can also be said that Figure 2 The stacked battery 10a shown has the following structure: a plurality of single cell layers 19 are stacked and electrically connected in parallel. In the stacked battery 10a, a restraining member (pressing member) applies a restraining pressure (not shown) in the stacking direction of the power generation element 21. Therefore, the volume of the power generation element 21 remains unchanged.
[0025] like Figure 2As shown, in the outermost negative electrode current collector located at the two outermost layers of the power generation element 21, the negative electrode active material layer 13 is only arranged on any single side, but the active material layer can also be arranged on both sides. That is, not only is a current collector dedicated to the outermost layer provided with an active material layer only on one side, but a current collector having active material layers on both sides can also be used directly as the outermost current collector.
[0026] The negative electrode collector 11' and the positive electrode collector 11" have the following structure: a negative electrode collector plate (tab) 25 and a positive electrode collector plate (tab) 27 that are electrically connected to each electrode (positive electrode and negative electrode) are respectively installed, and are led out to the outside of the laminate film 29 in a manner of being clamped at the end of a laminate film 29 that serves as an outer packaging material for the battery. The positive electrode collector plate 27 and the negative electrode collector plate 25 can be respectively installed on the positive electrode collector 11" and the negative electrode collector 11' of each electrode through ultrasonic welding, resistance welding, etc. via a positive electrode lead and a negative electrode lead (not shown) as required.
[0027] Figure 3 Schematic diagram of the cross-section of the positive electrode of this embodiment. Figure 3 As described above, the positive electrode 14 has a structure in which the positive electrode active material layer 15 is arranged on the surface of the positive electrode collector 11 ″. Figure 3 Although not shown in the figure, the exposed surface of the positive electrode active material layer 15 that is not in contact with the positive electrode current collector 11" is connected to the solid electrolyte layer 17 (see Figure 2 ) is in contact. The positive electrode active material layer 15 has a structure formed by stacking a first layer 15a and a second layer 15b, wherein the first layer 15a is in contact with the solid electrolyte layer 17 and contains a positive electrode active material, a solid electrolyte and a binder, and the second layer 15b is in contact with the positive electrode collector 11" and contains a positive electrode active material and a binder.
[0028] Hereinafter, main components of the secondary battery of this embodiment will be described.
[0029] [Current Collector]
[0030] The current collector (negative electrode current collector 11' and positive electrode current collector 11") has the function of mediating the movement of electrons from the electrode active material layer. There is no particular limitation on the material constituting the current collector. As the constituent material of the current collector, for example, metals and conductive resins can be used.
[0031] Specifically, metals include aluminum, nickel, iron, stainless steel, titanium, copper, etc. In addition to these, cladding materials of nickel and aluminum, cladding materials of copper and aluminum, etc. can also be used. In addition, it can also be a foil formed by covering aluminum on the metal surface. Among them, aluminum, stainless steel, copper, and nickel are preferred from the viewpoints of electronic conductivity, battery operating potential, and adhesion of active materials.
[0032] Examples of the latter conductive resin include a conductive polymer material or a non-conductive polymer material to which a conductive filler is added as needed.
[0033] It should be noted that the current collector may be a single-layer structure formed of a single material, or may be a laminated structure of layers formed of these materials in an appropriate combination. From the perspective of lightweighting the current collector, it is preferred to include a conductive resin layer formed of a resin having at least conductivity. In addition, from the perspective of cutting the movement of lithium ions between single cell layers, a metal layer may be provided on a portion of the current collector.
[0034] [Negative electrode (negative electrode active material layer)]
[0035] exist Figure 1 and Figure 2 In the stacked battery of the embodiment shown, the negative electrode active material layer 13 contains a negative electrode active material. There is no particular limitation on the type of negative electrode active material, and examples thereof include: carbon materials, metal oxides, and metal active materials. In addition, as the negative electrode active material, a metal containing lithium can be used. Such a negative electrode active material is not particularly limited as long as it is an active material containing lithium. In addition to metallic lithium, lithium-containing alloys can also be listed. As lithium-containing alloys, for example, alloys of Li and at least one of In, Al, Si, Sn, Mg, Au, Ag, and Zn can be listed. The negative electrode active material preferably contains metallic lithium or a lithium-containing alloy, a silicon-based negative electrode active material, or a tin-based negative electrode active material, and particularly preferably contains metallic lithium or a lithium-containing alloy. It should be noted that when metallic lithium or a lithium-containing alloy is used as the negative electrode active material, the secondary battery of this embodiment can be a so-called lithium precipitation type secondary battery in which lithium metal as a negative electrode active material is precipitated on the negative electrode collector during charging. Therefore, in this method, the thickness of the negative electrode active material layer increases as the charging process proceeds, and the thickness of the negative electrode active material layer decreases as the discharging process proceeds. The negative electrode active material layer may not exist during full discharge, but depending on the situation, a certain degree of negative electrode active material layer formed of lithium metal may be configured during full discharge.
[0036] The content of the negative electrode active material in the negative electrode active material layer is not particularly limited, but is, for example, preferably in the range of 40 to 99 mass %, and more preferably in the range of 50 to 90 mass %.
[0037] The negative electrode active material layer also preferably includes a solid electrolyte. By including a solid electrolyte in the negative electrode active material layer, the ion conductivity of the negative electrode active material layer can be improved. Examples of solid electrolytes include sulfide solid electrolytes and oxide solid electrolytes, preferably sulfide solid electrolytes. It should be noted that in this specification, a solid electrolyte refers to a material composed mainly of an ion conductor that can conduct ions in a solid, and in particular refers to a material having a lithium ion conductivity of 1×10 -5 S / cm or more, the lithium ion conductivity is preferably 1×10 -4 Here, the value of ion conductivity can be measured by an AC impedance method.
[0038] Examples of the sulfide solid electrolyte include LiI-Li2S-SiS2, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, LiI-Li3PS4, LiI-LiBr-Li3PS4, Li3PS4, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are positive numbers, and Z is any of Ge, Zn, and Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (wherein x and y are positive numbers, and M is any of P, Si, Ge, B, Al, Ga, and In), etc. It should be noted that the description of "Li2S-P2S5" means a sulfide solid electrolyte formed using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions.
[0039] The sulfide solid electrolyte may have, for example, a Li3PS4 skeleton, a Li4P2S7 skeleton, or a Li4P2S6 skeleton. Examples of sulfide solid electrolytes having a Li3PS4 skeleton include LiI-Li3PS4, LiI-LiBr-Li3PS4, and Li3PS4. In addition, examples of sulfide solid electrolytes having a Li4P2S7 skeleton include Li-PS-based solid electrolytes called LPS (e.g., Li7P3S 11 ). In addition, as a sulfide solid electrolyte, for example, Li(4-x) Ge (1-x) P x S4 (x satisfies 0<x<1) represented by LGPS, etc. Among them, the sulfide solid electrolyte contained in the active material layer is preferably a sulfide solid electrolyte containing the P element, and the sulfide solid electrolyte is more preferably a material with Li2S-P2S5 as the main component. The sulfide solid electrolyte may also contain halogen (F, Cl, Br, I). In a preferred embodiment, the sulfide solid electrolyte contains Li6PS5X (here, X is Cl, Br or I, preferably Cl).
[0040] In addition, when the sulfide solid electrolyte is a Li2S-P2S5 system, the ratio of Li2S and P2S5 is preferably in the range of Li2S:P2S5=50:50 to 100:0 in terms of molar ratio, among which Li2S:P2S5=70:30 to 80:20 is preferred.
[0041] In addition, the sulfide solid electrolyte may be sulfide glass, crystallized sulfide glass, or a crystalline material obtained by a solid phase method. It should be noted that sulfide glass can be obtained, for example, by mechanically grinding (ball milling, etc.) the raw material composition. In addition, crystallized sulfide glass can be obtained, for example, by heat treating sulfide glass at a temperature above the crystallization temperature.
[0042] As the oxide solid electrolyte, for example, a compound having a NASICON structure can be cited. As an example of a compound having a NASICON structure, the following can be cited: 1+x Al x Ge 2-x Compounds represented by (PO4)3(0≤x≤2) (LAGP), general formula Li 1+x Al x Ti 2-x (PO4)3 (0≤x≤2) represented by a compound (LATP) etc. In addition, other examples of oxide solid electrolytes include: LiLaTiO (for example, Li 0.34 La 0.51 TiO3), LiPON (e.g., Li 2.9 PO 3.3 N 0.46 ), LiLaZrO (e.g., Li7La3Zr2O 12 )wait.
[0043] As the shape of the solid electrolyte, for example, there can be listed: granular shapes such as a true sphere and an ellipsoid, a thin film, etc. In the case where the solid electrolyte is granular, its average particle size (D50) is not particularly limited, but is preferably 40 μm or less, more preferably 20 μm or less, and further preferably 10 μm or less. On the other hand, the average particle size (D50) is preferably 0.01 μm or more, and more preferably 0.1 μm or more.
[0044] The content of the solid electrolyte in the negative electrode active material layer is, for example, preferably in the range of 1 to 60 mass %, more preferably in the range of 10 to 50 mass %.
[0045] The negative electrode active material layer may contain at least one of a binder and a conductive aid in addition to the negative electrode active material and the solid electrolyte.
[0046] The binder is not particularly limited, and examples thereof include: thermoplastic polymers such as polybutylene terephthalate, polyethylene terephthalate, polyvinylidene fluoride (PVDF) (including compounds in which hydrogen atoms are substituted by other halogen elements), polyethylene, polypropylene, polymethylpentene, polybutene, polyether nitrile, polytetrafluoroethylene (PTFE), polyacrylonitrile, polyimide, polyamide, ethylene-vinyl acetate copolymer, polyvinyl chloride, styrene / butadiene rubber (SBR), ethylene / propylene / diene copolymer, styrene / butadiene / styrene block copolymer and hydrogenated products thereof, styrene / isoprene / styrene block copolymer and hydrogenated products thereof, tetrafluoroethylene / hexafluoropropylene copolymer (FEP), tetrafluoroethylene / perfluoroalkyl vinyl ether copolymer (PFA), ethylene / tetrafluoroethylene copolymer (E Fluorine resins such as TFE, polytrifluoroethylene (PCTFE), ethylene / chlorotrifluoroethylene copolymer (ECTFE), polyvinyl fluoride (PVF), vinylidene fluoride-hexafluoropropylene fluororubber (VDF-HFP fluororubber), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene fluororubber (VDF-HFP-TFE fluororubber), vinylidene fluoride-pentafluoropropylene fluororubber (VDF-PFP fluororubber), vinylidene fluoride-pentafluoropropylene-tetrafluoroethylene fluororubber (VDF-PFP-TFE fluororubber), vinylidene fluoride-perfluoromethyl vinyl ether-tetrafluoroethylene fluororubber (VDF-PFMVE-TFE fluororubber), vinylidene fluoride-chlorotrifluoroethylene fluororubber (VDF-CTFE fluororubber), epoxy resin, carboxymethyl cellulose, etc. Among them, polyimide, styrene / butadiene rubber, carboxymethyl cellulose, polypropylene, polytetrafluoroethylene, polyacrylonitrile, and polyamide are more preferred.
[0047] There are no particular restrictions on the conductive aid, and examples thereof include: metals such as aluminum, stainless steel (SUS), silver, gold, copper, titanium, alloys containing these metals, or metal oxides; carbon fibers (specifically, vapor deposited carbon fibers (VGCF), polyacrylonitrile-based carbon fibers, pitch-based carbon fibers, rayon-based carbon fibers, activated carbon fibers, etc.), carbon nanotubes (CNTs), carbon black (specifically, acetylene black, Ketjen black (registered trademark), furnace black, channel black, hot lamp black, etc.), and other carbons, but are not limited to these. In addition, those obtained by coating the above-mentioned metal materials around granular ceramic materials and resin materials by plating or the like can also be used as conductive aids. Among these conductive aids, from the viewpoint of electrical stability, it is preferred to include at least one selected from the group consisting of aluminum, stainless steel, silver, gold, copper, titanium, and carbons, more preferably to include at least one selected from the group consisting of aluminum, stainless steel, silver, gold, and carbons, and further preferably to include at least one carbon. These conductive aids can be used alone or in combination of two or more. The electronic conductivity of the conductive additive is preferably 1 S / m or more, more preferably 1×10 2 S / m or more, more preferably 1×10 4 S / m or more, more preferably 1×10 5 S / m or more. The upper limit of the electronic conductivity of the conductive additive is not particularly limited, but is usually 1×10 7 S / m or less.
[0048] The conductive agent is preferably in the form of particles or fibers. When the conductive agent is in the form of particles, the particle shape is not particularly limited and may be any shape such as powder, sphere, rod, needle, plate, column, amorphous, scaly, or spindle.
[0049] The average particle size (primary particle size) of the conductive auxiliary agent when it is in a granular form is not particularly limited, but is preferably 0.01 to 10 μm from the viewpoint of the electrical characteristics of the battery. It should be noted that in this specification, the "particle size of the conductive auxiliary agent" refers to the maximum distance L between any two points on the contour line of the conductive auxiliary agent. As the value of the "average particle size of the conductive auxiliary agent", a value calculated as the average value of the particle sizes of particles observed in several to dozens of fields of view using an observation method such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM) is used.
[0050] When the negative electrode active material layer contains a conductive aid, the content of the conductive aid in the negative electrode active material layer is not particularly limited, and is preferably 0 to 10% by mass, more preferably 2 to 8% by mass, and further preferably 4 to 7% by mass relative to the total mass of the negative electrode active material layer. If it is within such a range, a more solid electron conduction path can be formed in the negative electrode active material layer, which can contribute to the effective improvement of battery characteristics.
[0051] The thickness of the negative electrode active material layer varies depending on the structure of the target secondary battery, but is preferably within a range of 0.1 to 1000 μm, for example.
[0052] [Solid electrolyte layer]
[0053] exist Figure 1 and Figure 2 In the stacked battery of the illustrated embodiment, the solid electrolyte layer 17 is interposed between the positive electrode active material layer and the negative electrode active material layer and is a layer that essentially contains a solid electrolyte.
[0054] There are no particular limitations on the specific form of the solid electrolyte contained in the solid electrolyte layer, and the solid electrolytes and preferred forms thereof exemplified in the column of the negative electrode active material layer may be used. Depending on the circumstances, solid electrolytes other than the above-mentioned solid electrolytes may also be used in combination.
[0055] The solid electrolyte layer may contain a binder in addition to the above-mentioned solid electrolyte.
[0056] The thickness of the solid electrolyte layer varies according to the composition of the target lithium secondary battery. From the viewpoint of improving the volume energy density of the battery, it is preferably 600 μm or less, more preferably 500 μm or less, and further preferably 400 μm or less. On the other hand, there is no particular restriction on the lower limit of the thickness of the solid electrolyte layer, but it is preferably 1 μm or more, more preferably 5 μm or more, and further preferably 10 μm or more.
[0057] [Positive electrode active material layer]
[0058] exist Figure 1 and Figure 2 In the stacked battery of the embodiment shown, the positive electrode active material layer 15 must contain a solid electrolyte and a binder. In addition, the positive electrode active material layer 15 has a structure formed by stacking a first layer and a second layer, wherein the first layer is in contact with the solid electrolyte layer 17 and the second layer is in contact with the negative electrode active material layer 13.
[0059] (1) Layer 1
[0060] In the positive electrode active material layer, the first layer is arranged so as to be in contact with the solid electrolyte layer. The first layer must contain a positive electrode active material, a solid electrolyte, and a binder.
[0061] (Positive electrode active material)
[0062] There are no particular restrictions on the type of positive electrode active material contained in the first layer, and examples thereof include layered rock salt type active materials such as LiCoO2, LiMnO2, LiNiO2, LiVO2, Li(Ni-Mn-Co)O2, LiMn2O4, LiNi0.5 Mn 1.5 O4 and other spinel active materials, LiFePO4, LiMnPO4 and other olivine active materials, Li2FeSiO4, Li2MnSiO4 and other Si-containing active materials, etc. In addition, examples of oxide active materials other than the above include Li4Ti5O 12 . Among them, it is preferred to use a composite oxide containing lithium and nickel, and it is further preferred to use Li(Ni-Mn-Co)O2 and oxides in which a part of these transition metals is replaced by other elements (hereinafter, also referred to as "NMC composite oxide"). NMC composite oxide has a layered crystalline structure in which lithium atomic layers and transition metal (Mn, Ni and Co are regularly arranged) atomic layers are alternately stacked with oxygen atomic layers sandwiched between them. Each atom of the transition metal M contains one Li atom, and the amount of Li extracted is twice that of spinel lithium manganese oxide, that is, the supply capacity is doubled, and high capacity can be maintained.
[0063] As described above, NMC composite oxides also include composite oxides in which a part of transition metal elements is replaced by other metal elements. In this case, other elements include Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, Sn, V, Cu, Ag, Zn, etc., preferably Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, more preferably Ti, Zr, P, Al, Mg, Cr, and from the viewpoint of improving cycle characteristics, more preferably Ti, Zr, Al, Mg, Cr.
[0064] Furthermore, the use of a sulfur-based positive electrode active material is also one of the preferred embodiments. Examples of the sulfur-based positive electrode active material include particles or films of organic sulfur compounds or inorganic sulfur compounds, as long as they can release lithium ions during charging and absorb lithium ions during discharging by utilizing the redox reaction of sulfur.
[0065] Depending on the situation, two or more positive electrode active materials may be used in combination. Of course, positive electrode active materials other than those described above may also be used.
[0066] The shape of the positive electrode active material includes, for example, a particle shape (spherical shape, fibrous shape), a thin film shape, etc. When the positive electrode active material is in a particle shape, the average particle size (D 50 ) is preferably in the range of 1 nm to 100 μm, more preferably in the range of 10 nm to 50 μm, further preferably in the range of 100 nm to 20 μm, and particularly preferably in the range of 1 to 20 μm. It should be noted that in this specification, the average particle size (D 50 ) can be measured by laser diffraction scattering method.
[0067] The content of the positive electrode active material in the first layer is not particularly limited, but is preferably greater than 50% by mass, more preferably greater than 50% by mass and within the range of 95% by mass or less, and further preferably greater than 60% by mass and within the range of 90% by mass or less, relative to 100% by mass of the total solid content contained in the first layer.
[0068] (Solid Electrolyte)
[0069] The type of solid electrolyte contained in the first layer is not particularly limited, but a sulfide solid electrolyte is more preferably contained. Specific aspects and preferred aspects of the solid electrolyte such as the sulfide solid electrolyte can be similarly those described in the section of the solid electrolyte layer.
[0070] The content of the solid electrolyte in the first layer must be 1% by mass or more relative to 100% by mass of all solid components contained in the first layer. If the content of the solid electrolyte in the first layer is less than 1% by mass, the internal resistance of the battery will increase due to the low ion conductivity of the first layer, and it may be impossible to obtain sufficient fast charging characteristics. The content of the solid electrolyte in the first layer is preferably 1% by mass or more and 70% by mass or less, more preferably 5% by mass or more and 50% by mass or less, and further preferably 10% by mass or more and 30% by mass or less. If the content of the solid electrolyte in the first layer is within the above range, both the ion conductivity and the energy density of the first layer can be taken into account.
[0071] (Adhesive)
[0072] There is no particular limitation on the type of binder contained in the first layer, and the binder described in the column of the negative electrode active material layer can also be used. Among them, the binder contained in the first layer preferably contains a fibrous binder. In more detail, when the cross section of the first layer is observed using a scanning electron microscope (SEM), the area of the fibrous binder in the observed image accounts for a proportion of the total area of the binder that is preferably greater than 50%, more preferably 80% or more and 100% or less, further preferably 90% or more and 100% or less, particularly preferably 95% or more and 100% or less, and most preferably 100%. If the area ratio of the fibrous binder in the first layer is within the above range, the contact area between the particles of the positive electrode active material and the solid electrolyte, and any conductive aid included becomes larger, so the internal resistance of the battery remains low, and the fast charging characteristics can be further improved. It should be noted that in this specification, "a cross section of a layer" refers to a cross section when the layer is cut along the stacking direction of the secondary battery (i.e., a cross section when the layer is cut along the thickness direction). In addition, in this specification, "fibrous binder" means a binder mainly composed of fibers having an aspect ratio of 10 or more and a minimum Feret diameter of 0.2 μm or less in the observed image when a cross section of a positive electrode active material layer is observed using a scanning electron microscope (SEM). It should be noted that the aspect ratio refers to a value calculated by dividing the maximum Feret diameter by the minimum Feret diameter. The maximum Feret diameter refers to the maximum distance between two parallel straight lines when the contour of the binder is clamped by the straight lines, and the minimum Feret diameter refers to the minimum distance between the straight lines when the contour of the binder is clamped by two parallel straight lines. A binder "mainly composed of" the above-mentioned fibers means that the area of the above-mentioned fiber portion in the SEM observation image accounts for 50% or more of the total area of the binder. A fibrous binder may include a portion other than fibers having an aspect ratio of 10 or more and a minimum Feret diameter of 0.2 μm or less (a portion with an aspect ratio of less than 10 or a portion with a minimum Feret diameter of more than 0.2 μm). However, the area of the portion other than the fibers must be less than 50% of the total area of the fibrous adhesive in the SEM observation image, preferably less than 20%, more preferably less than 10%, and further preferably less than 5% (the lower limit is 0%). The fibrous adhesive includes not only an adhesive consisting of only one fiber, but also an adhesive having a structure in which two or more fibers are connected to each other. As specific shapes of the adhesive having a structure in which two or more fibers are connected to each other, branched, radial, and grid shapes, as well as shapes combining these, can be listed.
[0073] Here, a method for obtaining the maximum Feret diameter and the minimum Feret diameter in a binder having a structure in which two or more fibers are connected to each other will be described. Figure 4 This is a schematic diagram showing an example of a branched fibrous binder. Figure 4The adhesive 30 shown has a structure in which fibers X, Y, and Z are connected to each other. Each line segment represents a line connecting the center (1 / 2 width) of the width of the fibers, and points A, B, and C represent the ends of each line segment. It should be noted that the ends of each line segment coincide with the ends of the fibers. Point D represents the intersection of the three line segments. In other words, it can also be said that Figure 4 The adhesive 30 shown has a shape in which a fiber X from point A to point D, a fiber Y from point B to point D, and a fiber Z from point C to point D are bonded at point D. Figure 4 The maximum Feret's diameter of fiber X in the adhesive 30 shown is defined as the distance from point A to point D. Similarly, the maximum Feret's diameter of fiber Y is the distance from point B to point D, and the maximum Feret's diameter of fiber Z is the distance from point C to point D. In addition, the minimum Feret's diameter of fiber X is the minimum distance between two parallel straight lines when the contour of the adhesive (fiber) between point A and point D is clamped by the straight lines. The same applies to the minimum Feret's diameters of fiber Y and fiber Z. Figure 4 In the adhesive 30 shown, the fibers Y and Z have an aspect ratio of 10 or more and a minimum Feret diameter of 0.2 μm or less, and the aspect ratio of the fiber X is less than 10. However, the area of the fiber X portion accounts for less than 50% of the total area of the adhesive 30, so it can be said that Figure 4 The adhesive shown is a fibrous adhesive.
[0074] As the type of fibrous binder, as long as it is a fibrous binder with the above-mentioned shape in the positive electrode active material layer, there is no particular restriction, and an adhesive that is fibrillated by applying shear force can be appropriately used. As the type of such a fibrillated binder, polytetrafluoroethylene (PTFE), carboxymethyl cellulose, polyethylene oxide, polyvinyl alcohol, polyethylene, more preferably polytetrafluoroethylene (PTFE). By using such an adhesive, it becomes better to take into account the contact between the bonding properties and the particles, so that the fast charging characteristics can be further improved. The fibrous binder can be used alone or in combination with more than two kinds. It should be noted that in this specification, the record of the compound name of the binder is not only the compound represented by the compound name, but also the mode in which a part of the end or side chain is replaced (modified) by other substituents. In the case of a mode in which a part of the end or side chain is replaced (modified) by other substituents, the proportion of the constituent unit in which the end or side chain is replaced (modified) by other substituents to all constituent units 100 mol% is preferably 10 mol% or less, more preferably 5 mol% or less.
[0075] (Conductive additive)
[0076] The first layer may contain a conductive aid as required. There is no particular limitation on the type of conductive aid, and the conductive aids described in the column of the negative electrode active material layer may be used. The conductive aid contained in the first layer preferably contains fibrous carbon. It should be noted that in this specification, "fibrous carbon" refers to conductive carbon with an aspect ratio of 10 or more and a minimum Feret diameter of 0.2 μm or less in the observed image when observed using a scanning electron microscope (SEM). As described above, the electronic conductivity of the conductive carbon is preferably 1 S / m or more, and more preferably 1×10 2 S / m or more, more preferably 1×10 4 S / m or more, more preferably 1×10 5 S / m or more. The upper limit of the electronic conductivity of conductive carbon is not particularly limited, but is usually 1×10 7 S / m or less.
[0077] The type of fibrous carbon is not particularly limited as long as it has the above-mentioned shape, and examples thereof include carbon fibers (carbon nanofibers), graphene, and carbon nanotubes (single-layer carbon nanotubes and multi-layer carbon nanotubes). Among them, carbon fibers (carbon nanofibers) are preferred. The fibrous carbon may be used alone or in combination of two or more.
[0078] The content of fibrous carbon in the total amount of 100 mass % of the conductive aid contained in the first layer is preferably greater than 50 mass %, more preferably 80 mass % or more and 100 mass % or less, further preferably 90 mass % or more and 100 mass % or less, particularly preferably 95 mass % or more and 100 mass % or less, and most preferably 100 mass %.
[0079] The thickness of the first layer varies depending on the structure of the target secondary battery, but is preferably 50 μm to 120 μm, and more preferably 60 μm to 100 μm. When the thickness of the first layer is within the above range, sufficient energy density can be ensured.
[0080] There is no particular limitation on the method for manufacturing the first layer, and known methods may be appropriately referred to. For the first layer comprising a fibrous binder, a shear force is applied to a mixture comprising a positive electrode active material, a solid electrolyte, a fibrillable binder, and a conductive aid (preferably fibrous carbon) added as needed, so that the binder is fibrillated. And, the first layer can be obtained by molding the fibrillated mixture into a sheet. It should be noted that the above-mentioned mixture is preferably a powdery mixture that does not substantially contain a liquid component. Relative to 100% by mass of the mixture, the content of the liquid component in the mixture is preferably 5% by mass or less, more preferably 3% by mass or less, further preferably 1% by mass or less, more preferably 0.5% by mass or less, particularly preferably 0.1% by mass or less, and most preferably 0% by mass.
[0081] (2) Layer 2
[0082] In the positive electrode active material layer, the second layer is arranged so as to be in contact with the positive electrode current collector. The second layer necessarily contains the positive electrode active material and the binder.
[0083] (Positive electrode active material)
[0084] As the type of positive electrode active material contained in the second layer, the positive electrode active material and its preferred embodiment exemplified in the column of the first layer can be used. It should be noted that the positive electrode active material contained in the first layer and the positive electrode active material contained in the second layer can be the same as each other or different, and are preferably the same as each other.
[0085] The content of the positive electrode active material in the second layer is not particularly limited, and relative to 100 mass% of the total solid content contained in the second layer, preferably exceeds 50 mass%, more preferably exceeds 50 mass% and is within the range of 95 mass% or less, and further preferably is within the range of 60 mass% or more and 90 mass% or less. If the content of the positive electrode active material in the second layer is within the above range, the energy density can be maintained.
[0086] (Adhesive)
[0087] There is no particular limitation on the type of binder contained in the second layer, and the binder described in the column of the negative electrode active material layer can also be used. Among them, the binder contained in the second layer preferably contains a non-fibrous binder. In more detail, when the cross section of the second layer is observed using a scanning electron microscope (SEM), the area of the non-fibrous binder in the observed image accounts for a proportion of the total area of the binder that is preferably greater than 50%, more preferably 80% or more and 100% or less, further preferably 90% or more and 100% or less, particularly preferably 95% or more and 100% or less, and most preferably 100% (that is, the area ratio of the fibrous binder is preferably less than 50%, more preferably 0% or more and 20% or less, further preferably 0% or more and 10% or less, particularly preferably 0% or more and 5% or less, and most preferably 0%). If the area ratio of the non-fibrous binder in the second layer is within the above range, the adhesion between the second layer and the positive electrode collector is improved, and the second layer can be prevented from peeling off from the positive electrode collector. As a result, the internal resistance of the battery remains low, and the fast charging characteristics can be further improved. It should be noted that in this specification, "non-fibrous binder" refers to a binder other than the above-mentioned "fibrous binder". That is, in this specification, "non-fibrous binder" refers to a binder having an aspect ratio of less than 10 or a minimum Feret diameter of more than 0.2 μm in the observed image when the cross-section of the positive electrode active material layer is observed using a scanning electron microscope (SEM). Whether it is a "non-fibrous binder" is determined by the method described in the examples described later, and the "area ratio of the non-fibrous binder" is calculated.
[0088] As the type of non-fibrous binder, as long as it is a binder with the above-mentioned shape in the positive electrode active material layer, there is no particular limitation, preferably styrene / butadiene rubber (SBR), polyvinylidene fluoride (PVDF), ethyl cellulose, acrylic resin, more preferably polyvinylidene fluoride (PVDF). By using such an adhesive, the second layer can be firmly fitted to the positive electrode collector, so the fast charging characteristics can be further improved. The non-fibrous binder can be used alone or in combination of two or more. It should be noted that, as described above, the above-mentioned binder may include a method in which a portion of the end or side chain is replaced (modified) by other substituents.
[0089] (Conductive additive)
[0090] The second layer may contain a conductive aid as needed. There is no particular restriction on the type of the conductive aid, and the conductive aid described in the column of the above-mentioned negative electrode active material layer can also be used. Among them, the conductive aid contained in the second layer preferably contains fibrous carbon. There is no particular restriction on the type of the conductive aid, and the conductive aid described in the column of the above-mentioned first layer can also be used. It should be noted that the conductive aid contained in the first layer (preferably fibrous carbon) and the conductive aid contained in the second layer (preferably fibrous carbon) may be the same as or different from each other, and are preferably the same as each other.
[0091] The content of fibrous carbon in the total amount of 100 mass % of the conductive aid contained in the second layer is preferably greater than 50 mass %, more preferably 80 mass % or more and 100 mass % or less, further preferably 90 mass % or more and 100 mass % or less, particularly preferably 95 mass % or more and 100 mass % or less, and most preferably 100 mass %.
[0092] (Solid Electrolyte)
[0093] In the present invention, the second layer has the following characteristics: it does not contain a solid electrolyte or even if it is contained, it is a very small amount. In more detail, relative to the total solid content 100% by mass contained in the second layer, the content of the solid electrolyte in the second layer is 0% by mass or more than 0% by mass and less than 1% by mass. If the content of the solid electrolyte contained in the second layer is more than 1% by mass, there is a situation where the fast charging characteristics are insufficient. It is believed that when the potential of the positive electrode collector rises during charging, the solid electrolyte in contact with the positive electrode collector in the second layer deteriorates due to oxidation, causing the internal resistance of the battery to rise. For such reasons, relative to the total solid content 100% by mass contained in the second layer, the content of the solid electrolyte in the second layer is preferably 0% by mass or more than 0% by mass and less than 0.5% by mass, more preferably 0% by mass or more than 0% by mass and less than 0.1% by mass, and particularly preferably 0% by mass.
[0094] When the second layer includes a solid electrolyte, the type of solid electrolyte is not particularly limited, but a sulfide solid electrolyte is more preferably included. For the specific form and preferred form of the solid electrolyte such as a sulfide solid electrolyte, the solid electrolyte described in the column of the solid electrolyte layer can also be used. It should be noted that the solid electrolyte included in the first layer and the solid electrolyte included in the second layer may be the same as each other or different, and are preferably the same as each other.
[0095] The thickness of the second layer is preferably 0.1 μm or more and less than 5 μm, more preferably 1 μm or more and 4 μm or less. If the thickness of the second layer is 0.1 μm or more, the degradation of the solid electrolyte can be effectively suppressed, thereby preventing the increase of the internal resistance of the battery. If the thickness of the second layer is less than 5 μm, the energy density can be maintained.
[0096] The manufacturing method of the second layer is not particularly limited, and known methods can be appropriately referred to. As an example, a dispersion medium is appropriately added to the positive electrode active material, the binder, the conductive aid added as needed (preferably fibrous carbon) and the solid electrolyte added as needed to prepare a slurry. The slurry is applied to a support (for example, a positive electrode collector) and the dispersion medium is removed, so that the second layer can be obtained. If other examples are listed, a mixture comprising a positive electrode active material, a binder, a conductive aid added as needed (preferably fibrous carbon) and a solid electrolyte added as needed is kneaded and formed into a sheet, so that the second layer can be obtained. In this case, the above-mentioned mixture preferably does not substantially contain a liquid component, and the preferred mode of the content of the liquid component in the mixture is the same as that of the mixture in the manufacture of the above-mentioned first layer.
[0097] In the secondary battery of this embodiment, at least one of the first layer and the second layer preferably contains a conductive aid formed of fibrous carbon, and preferably both the first layer and the second layer contain a conductive aid formed of fibrous carbon. By containing fibrous carbon as a conductive aid in the first layer and / or the second layer, the internal resistance of the battery is kept low, and the fast charging characteristics can be further improved.
[0098] The secondary battery of this mode is particularly preferred: in the first layer, the binder contains a fibrous binder, and when the cross section of the first layer is observed using a scanning electron microscope, the area of the fibrous binder in the observed image accounts for more than 50% of the area of the binder; in the second layer, the binder contains a non-fibrous binder, and when the cross section of the second layer is observed using a scanning electron microscope, the area of the non-fibrous binder in the observed image accounts for more than 50% of the area of the binder; both the first layer and the second layer further contain a conductive additive formed of fibrous carbon, the fibrous binder contains polytetrafluoroethylene, and the non-fibrous binder contains polyvinylidene fluoride. As shown in Example 1 described later, due to the above-mentioned structure, particularly excellent rapid charging characteristics are exerted.
[0099] In the secondary battery of this embodiment, the positive electrode active material layer may include one or more other layers between the first layer and the second layer, and the first layer and the second layer are preferably disposed adjacent to each other.
[0100] [Positive electrode collector plate and negative electrode collector plate]
[0101] The material constituting the collector plate (25, 27) is not particularly limited, and known highly conductive materials used as collector plates for secondary batteries in the past can be used. As the constituent material of the collector plate, for example, metal materials such as aluminum, copper, titanium, nickel, stainless steel (SUS), and alloys thereof are preferred. From the viewpoint of light weight, corrosion resistance, and high conductivity. Aluminum and copper are more preferred, and aluminum is particularly preferred. It should be noted that the positive collector plate 27 and the negative collector plate 25 can use the same material or different materials.
[0102] [Positive lead and negative lead]
[0103] In addition, although the figure is omitted, the collector and the collector plate can be electrically connected via a positive lead and a negative lead. As the constituent material of the positive and negative leads, the materials used in known lithium secondary batteries can also be used. It should be noted that the portion taken out from the outer body is preferably covered with a heat-resistant insulating heat shrink tube, etc., so that it will not leak due to contact with surrounding equipment, wiring, etc., thereby affecting the product (such as automotive parts, particularly electronic equipment, etc.).
[0104] [Battery exterior materials]
[0105] As the battery outer material, in addition to the known metal can shell, other materials such as Figure 1 and Figure 2 As shown in the figure, a bag-shaped shell using a laminate film 29 containing aluminum can cover the power generation element. For the laminate film, for example, a laminate film of a three-layer structure in which PP, aluminum, and nylon are laminated in this order can be used, and there is no restriction on these. From the perspective of high output, excellent cooling performance, and being applicable to batteries for large devices for EV and HEV, the laminate film is ideal. In addition, since the group pressure applied to the power generation element from the outside can be easily adjusted, the outer body is more preferably a laminate film containing aluminum.
[0106] The stacked battery of this embodiment has a structure in which a plurality of single cell layers are connected in parallel, and therefore has a high capacity and excellent cycle durability. Therefore, the stacked battery of this embodiment can be suitably used as a driving power source for EVs and HEVs.
[0107] As mentioned above, although one embodiment of the secondary battery of the present invention has been described, the present invention is not limited to the configuration described in the above embodiment, and can be appropriately modified based on the description of the scope of the claims.
[0108] Example
[0109] The present invention is described in more detail below by way of examples. However, the technical scope of the present invention is not limited to the following examples. It should be noted that the following instruments and devices used in the glove box have been fully dried in advance.
[0110] <Production Example of Evaluation Battery Cell>
[0111] [Example 1]
[0112] (Manufacturing of Positive Electrode Active Material Layer)
[0113] (1) Manufacturing of the first layer
[0114] As the constituent material of the first layer, NMC composite oxide (LiNi 0.8 Mn 0.1 Co 0.1 O2, average particle size (D50): 1μm), argyrodite-type sulfide solid electrolyte (Li6PS5Cl, average particle size (D50): 0.2μm) as solid electrolyte, carbon nanofiber (CNF) as conductive aid (Showa Denko K.K., VGCF (registered trademark), aspect ratio: 60, average fiber diameter: about 150nm, average fiber length: about 9μm), and polytetrafluoroethylene (PTFE) as fibrillable binder. In a glove box with an argon atmosphere at a dew point below -68°C, the positive electrode active material, solid electrolyte, conductive aid and binder are weighed in a mass ratio of 79:16:3:2 and kneaded in an agate mortar. After confirming that the binder has been fibrillated, the obtained mixture is formed into a sheet with a hand pressure roller and then punched into a circle with a diameter of 19mm to obtain a first layer with a thickness of 80μm.
[0115] (2) Manufacturing of the second layer
[0116] As the constituent material of the second layer, NMC composite oxide (LiNi 0.8 Mn 0.1 Co 0.1 O2, average particle size (D50): 1μm), carbon nanofibers (CNF) as a conductive aid (Showa Denko K.K., VGCF (registered trademark), aspect ratio: 60, average fiber diameter: about 150nm, average fiber length: about 9μm), and polyvinylidene fluoride (PVDF) as a binder. In a glove box with an argon atmosphere at a dew point below -68°C, the positive electrode active material, the conductive aid and the binder were weighed in a mass ratio of 79:19:2 and kneaded in an agate mortar. The obtained mixture was formed into a sheet with a hand pressure roller and then punched into a circle with a diameter of 19mm to obtain a second layer with a thickness of 3μm.
[0117] (Manufacturing of Solid Electrolyte Layer)
[0118] In a glove box with an argon atmosphere at a dew point below -68°C, 95 parts by mass of a argon-type sulfide solid electrolyte (Li6PS5Cl) as a solid electrolyte was mixed with a binder solution (a solution of 5 parts by mass of styrene-butadiene rubber (SBR) as a binder dissolved in meta-trimethylbenzene as a solvent) to prepare a solid electrolyte slurry. The obtained solid electrolyte slurry was applied to the surface of a stainless steel foil as a support with an applicator, and after drying, it was punched into a circle with a diameter of 25 mm to obtain a solid electrolyte layer with a thickness of 40 μm.
[0119] (Manufacturing of negative electrode intermediate layer)
[0120] Silver nanoparticles and carbon black nanoparticles were weighed and mixed in a mass ratio of 1:3. 5 parts by mass of the obtained mixture were added to a binder solution (a solution prepared by dissolving 0.5 parts by mass of styrene-butadiene rubber (SBR) as a binder in mesitylene as a solvent) and mixed to prepare a negative electrode intermediate layer slurry. The obtained negative electrode intermediate layer slurry was applied to the surface of a stainless steel foil as a negative electrode collector with an applicator, and after drying, it was punched into a circle with a diameter of 21 mm to obtain a negative electrode intermediate layer with a thickness of 10 μm.
[0121] (Manufacturing of Evaluation Battery Cell)
[0122] The second layer and the first layer manufactured above were sequentially overlapped on an aluminum foil (circular with a diameter of 19 mm) as a positive electrode collector. Furthermore, on the first layer, the solid electrolyte layer formed on the surface of the stainless steel foil manufactured above was transferred by cold isostatic pressing (CIP) in a manner that the exposed surface of the solid electrolyte layer was opposite to the first layer. After peeling off the stainless steel foil adjacent to the solid electrolyte layer, the negative electrode intermediate layer formed on the surface of the stainless steel foil (negative electrode collector) manufactured above was overlapped on the transferred solid electrolyte layer in a manner that the exposed surface of the negative electrode intermediate layer was opposite to the solid electrolyte layer, and pressurized by cold isostatic pressing (CIP), thereby obtaining a battery cell for evaluation (lithium precipitation type all-solid-state lithium secondary battery).
[0123] [Example 2]
[0124] In “(2) Production of the second layer”, a battery cell for evaluation of this example was produced in the same manner as in Example 1 except that styrene-butadiene rubber (SBR) was used as the binder instead of polyvinylidene fluoride (PVDF).
[0125] [Example 3]
[0126] In “(2) Production of the second layer”, the evaluation battery cell of this example was produced using the same method as in Example 2, except that acetylene black (manufactured by Denka Corporation, DENKA BLACK (registered trademark) HS-100, average primary particle size: 36 nm, aspect ratio less than 10) was used instead of carbon nanofibers (CNF) as a conductive additive.
[0127] [Comparative Example 1]
[0128] (Manufacturing of Positive Electrode Active Material Layer)
[0129] As the constituent material of the positive electrode active material layer, NMC composite oxide (LiNi 0.8 Mn 0.1 Co 0.1 O2, average particle size (D50): 1μm), argyrodite-type sulfide solid electrolyte (Li6PS5Cl, average particle size (D50): 0.2μm) as solid electrolyte, acetylene black (Denka Corporation, DENKABLACK (registered trademark) HS-100, average primary particle size: 36nm, aspect ratio less than 10) as conductive aid, polytetrafluoroethylene (PTFE; fibrillable) and polyvinylidene fluoride (PVDF) as binders. In a glove box with an argon atmosphere at a dew point below -68°C, the positive electrode active material, solid electrolyte, conductive aid and binder are weighed in a mass ratio of 79:16:3:2 (the mass ratio of PTFE and PVDF is 1:1), and kneaded in an agate mortar. After confirming that the PTFE has been fibrillated, the obtained mixture is formed into a sheet with a hand pressure roller and then punched into a circle with a diameter of 19mm, thereby obtaining a positive electrode active material layer with a thickness of 83μm.
[0130] A battery cell for evaluation of this comparative example was produced in the same manner as in Example 1 except that the positive electrode active material layer obtained above was used.
[0131] [Comparative Example 2]
[0132] In the above-mentioned "(Manufacture of positive electrode active material layer)", the evaluation battery cell of this comparative example is manufactured by the same method as in comparative example 1, except that only polyvinylidene fluoride (PVDF) is used as a binder instead of polytetrafluoroethylene (PTFE); the positive electrode active material, solid electrolyte, conductive aid and binder are weighed in a mass ratio of 79:16:3:2 and kneaded in an agate mortar.
[0133] [Comparative Example 3]
[0134] In the above "(Manufacturing of positive electrode active material layer)", except that carbon nanofiber (CNF) (manufactured by Showa Denko K.K., VGCF (registered trademark), aspect ratio: 60, average fiber diameter: about 150 nm, average fiber length: about 9 μm) is used instead of acetylene black as a conductive auxiliary agent; polytetrafluoroethylene (PTFE) is used as a binder instead of polyvinylidene fluoride (PVDF); the positive electrode active material, solid electrolyte, conductive auxiliary agent and binder are weighed in a mass ratio of 79:16:3:2 and kneaded in an agate mortar. The battery cell for evaluation of this comparative example is manufactured by the same method as in Comparative Example 1.
[0135] [Comparative Example 4]
[0136] (Manufacturing of Positive Electrode Active Material Layer)
[0137] (1) Manufacturing of the first layer
[0138] As the constituent material of the first layer, NMC composite oxide (LiNi 0.8 Mn 0.1 Co 0.1 O2, average particle size (D50): 1μm), argyrodite-type sulfide solid electrolyte (Li6PS5Cl, average particle size (D50): 0.2μm) as solid electrolyte, carbon nanofiber (CNF) as conductive aid (Showa Denko K.K., VGCF (registered trademark), aspect ratio: 60, average fiber diameter: about 150nm, average fiber length: about 9μm), and polytetrafluoroethylene (PTFE) as fibrillable binder. In a glove box with an argon atmosphere at a dew point below -68°C, the positive electrode active material, solid electrolyte, conductive aid and binder are weighed in a mass ratio of 79:16:3:2 and kneaded in an agate mortar. After confirming that the binder has been fibrillated, the obtained mixture is formed into a sheet with a hand pressure roller and then punched into a circle with a diameter of 19mm to obtain a first layer with a thickness of 80μm.
[0139] (2) Manufacturing of the second layer
[0140] As the constituent material of the second layer, NMC composite oxide (LiNi 0.8 Mn 0.1 Co 0.1O2, average particle size (D50): 1μm), argyrodite-type sulfide solid electrolyte (Li6PS5Cl, average particle size (D50): 0.2μm) as a solid electrolyte, carbon nanofibers (CNF) as a conductive aid (Showa Denko K.K., VGCF (registered trademark), aspect ratio: 60, average fiber diameter: about 150nm, average fiber length: about 9μm), and polyvinylidene fluoride (PVDF) as a binder. In a glove box with an argon atmosphere at a dew point below -68°C, the positive electrode active material, solid electrolyte, conductive aid and binder are weighed in a mass ratio of 79:16:3:2 and kneaded in an agate mortar. The obtained mixture is formed into a sheet with a hand roller and then punched into a circle with a diameter of 19mm to obtain a second layer with a thickness of 3μm.
[0141] A battery cell for evaluation of this comparative example was produced in the same manner as in Example 1 except that the positive electrode active material layer obtained above was used.
[0142] [Comparative Example 5]
[0143] In the above "(Manufacturing of positive electrode active material layer)", the same method as in Comparative Example 1 was used except that carbon nanofibers (CNF) (manufactured by Showa Denko K.K., VGCF (registered trademark), aspect ratio: 60, average fiber diameter: about 150 nm, average fiber length: about 9 μm) were used instead of acetylene black as a conductive additive. A battery cell for evaluation of this comparative example was manufactured.
[0144] [Comparative Example 6]
[0145] In “(2) Production of the Second Layer”, a battery cell for evaluation of this comparative example was produced by the same method as in Example 1 except that the positive electrode active material was not used as the constituent material of the second layer.
[0146] <Observation of adhesive shape>
[0147] The positive electrode active material layer is taken out from the evaluation battery cell manufactured as described above, and the cross section of the first layer is observed using a scanning electron microscope (SEM). For each adhesive in the SEM image, the maximum Feret diameter and the minimum Feret diameter are obtained. In addition, the aspect ratio is calculated by dividing the maximum Feret diameter by the minimum Feret diameter. In addition, by confirming whether the area of the fiber portion with an aspect ratio of more than 10 and a minimum Feret diameter of less than 0.2 μm accounts for more than 50% of the total area of each adhesive, it is determined whether each adhesive is a fibrous adhesive or a non-fibrous adhesive. This operation is performed on SEM images of 10 fields of view (each field of view contains more than 10 adhesives), and the ratio of the area of the fibrous adhesive in the observed image to the area of the adhesive is calculated as a percentage. The results are shown in Table 1 below.
[0148] <Evaluation of fast charging characteristics>
[0149] The positive electrode collector and negative electrode collector of the evaluation battery cell manufactured as described above were connected to the positive electrode lead and the negative electrode lead, respectively, and three cycles of charge and discharge were performed according to the following charge and discharge test conditions. At this time, a pressure member was used to apply a restraining pressure of 3 MPa in the stacking direction of the evaluation battery cell, and the following charge and discharge test was performed.
[0150] (Charge and discharge test conditions)
[0151] 1) Charge and discharge conditions
[0152] [Voltage range] 3.0~4.3V
[0153] [Charging process] CCCV (0.01C cut-off)
[0154] [Discharge process]CC
[0155] [Charge and discharge rate] 0.1C or 2C
[0156] (After charging and discharging, pause for 30 minutes respectively)
[0157] 2) Evaluation temperature: 298K (25°C).
[0158] The battery cell for evaluation uses a charge and discharge tester. In a thermostatic chamber set to the above-mentioned evaluation temperature, during the charging process (lithium metal deposition on the negative electrode collector), it is set to constant current / constant voltage (CCCV) mode, and charged from 3.0V to 4.3V (0.01C cutoff) at the above-mentioned charge and discharge rate. Then, during the discharge process (lithium metal dissolution on the negative electrode collector), it is set to constant current (CC) mode, and discharged from 4.3V to 3.0V at the above-mentioned charge and discharge rate. Here, 1C means that if the current value is charged for 1 hour, the battery will just be in a fully charged (100% charged) state. Three cycles of charge and discharge treatment at 0.1C or 2C are performed respectively. In addition, the ratio of the charging capacity of the third cycle (2C) to the charging capacity of the third cycle (0.1C) is calculated, and the rapid charging characteristics are evaluated. The results are shown in Table 1 below.
[0159] [Table 1]
[0160]
[0161] As can be seen from the results shown in Table 1, according to the present invention, the rapid charging characteristics can be improved. The reason why the rapid charging characteristics of Comparative Example 4 are low is believed to be that when the content of the solid electrolyte in the second layer is high, when the potential of the positive electrode collector rises during charging, the solid electrolyte in the second layer in contact with the positive electrode collector deteriorates due to oxidation, and the internal resistance of the battery increases. In addition, the reason why the rapid charging characteristics of Comparative Example 6 are low is believed to be that when the positive electrode active material in the second layer does not exist, the potential of the second layer rises during charging, and the solid electrolyte in the first layer in contact with the second layer deteriorates due to oxidation, and the internal resistance of the battery increases.
[0162] By comparing Example 2 with Example 3, it is shown that the fast charging characteristics are further improved because both the first layer and the second layer contain fibrous carbon as a conductive aid. In addition, by comparing Example 1 with Example 2, it is shown that the fast charging characteristics are further improved because the first layer contains polytetrafluoroethylene as a fibrous binder and the second layer contains polyvinylidene fluoride as a non-fibrous binder.
[0163] Description of Reference Numerals
[0164] 10a, 100 stacked batteries,
[0165] 11' negative electrode collector,
[0166] 11” positive electrode collector,
[0167] 13 negative electrode active material layer,
[0168] 14 positive electrode,
[0169] 15 positive electrode active material layer,
[0170] 15a1st floor,
[0171] 15b Layer 2,
[0172] 17Solid electrolyte layer,
[0173] 19 single cell layers,
[0174] 21 Power generation element,
[0175] 25 negative electrode collector plate,
[0176] 27 positive electrode collector plate,
[0177] 29Laminating film,
[0178] 30 fibrous adhesives.
Claims
1. A secondary battery comprising a power generation element, The power generation element comprises: A positive electrode having a positive electrode active material layer disposed on the surface of a positive electrode current collector, Negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode and containing a solid electrolyte, The positive electrode active material layer is formed by stacking a first layer and a second layer, wherein the first layer is in contact with the solid electrolyte layer and contains a positive electrode active material, a solid electrolyte and a binder, and the second layer is in contact with the positive electrode collector and contains a positive electrode active material and a binder. The content of the solid electrolyte in the first layer is 1% by mass or more relative to 100% by mass of the total solid content contained in the first layer, The content of the solid electrolyte in the second layer is 0 mass % or exceeds 0 mass % and is less than 1 mass % relative to 100 mass % of the total solid content contained in the second layer.
2. The secondary battery according to claim 1, wherein In the first layer, the binder contains a fibrous binder, When a cross section of the first layer is observed using a scanning electron microscope, the ratio of the area of the fibrous binder in the observed image to the total area of the binder is greater than 50%.
3. The secondary battery according to claim 2, wherein: The fibrous binder includes at least one selected from the group consisting of polytetrafluoroethylene, carboxymethyl cellulose, polyethylene oxide, polyvinyl alcohol, and polyethylene.
4. The secondary battery according to claim 2 or 3, wherein: In the second layer, the adhesive comprises a non-fibrous adhesive, When a cross section of the second layer is observed using a scanning electron microscope, the ratio of the area of the non-fibrous binder in the observed image to the total area of the binder is greater than 50%.
5. The secondary battery according to claim 4, wherein The non-fibrous binder includes at least one selected from the group consisting of styrene / butadiene rubber, polyvinylidene fluoride, ethyl cellulose, and acrylic resin.
6. The secondary battery according to claim 1 or 2, wherein: At least one of the first layer and the second layer further contains a conductive auxiliary agent composed of fibrous carbon.
7. The secondary battery according to claim 4, wherein Both the first layer and the second layer further contain a conductive auxiliary agent formed of fibrous carbon, the fibrous binder contains polytetrafluoroethylene, and the non-fibrous binder contains polyvinylidene fluoride.
8. The secondary battery according to claim 1 or 2, wherein: The content of the positive electrode active material in the second layer exceeds 50% by mass with respect to 100% by mass of the total solid content contained in the second layer.
9. The secondary battery according to claim 1 or 2, wherein: The second layer has a thickness of 0.1 μm or more and less than 5 μm.
10. The secondary battery according to claim 1 or 2, wherein: The first layer has a thickness of 50 μm or more and 120 μm or less.
